Pemanfaatan Limbah Sabut Kelapa Menjadi Pot Bunga Untuk Menunjang Perekonomian Warga Desa Pengalihan Di Era Pandemi Covid-19 - Eliah Siregar; Muannif Ridwan; Indra Muchlis Adnan; Andriansyah Andriansyah; Sri Hidayanti; Herdiansyah Herdiansyah (Universitas Pahlawan Tuanku Tambusai, 2021)
This research discusses the use of coconut coir waste into flower pots to support the economy of the residents of Pengalihan Village in the era of the Covid-19 pandemic. The main income of the majority of the people of Pengalihan Village is from coconut plantations. As for what people produce from coconut plantations, only round coconut, white copra, and shell charcoal are produced, but currently the selling price of coconut has decreased slightly so that it affects people's income. Actually, the utilization of the results of the coconut plant is very large, one of which is from the coir itself. This study concludes that the use of coconut coir waste is very effective and can be an alternative choice to support the economy of the Pengalihan Village community in the Covid-19 Pandemic era. Coconut coir waste is one of the easily obtained biomass and is a by-product of agriculture. Coconut coir waste has the potential to be used as flower pots because it contains cellulose which in its molecular structure contains a carboxyl group and lignin which contains phenolic acid which is needed for plants.